2006
DOI: 10.5713/ajas.2006.672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Management Factors on Milk Production in First-calf Heifers

Abstract: The objective of this study was to investigate whether milk performance is impacted by the housing of heifers from the second to the seventh day of life, the method of feeding milk from the second week of life to weaning, the sire lineage and by the season of birth and season of calving. From 32 Holstein heifer-calves, which spent their first day of life in a loose housing maternity pen with their mother, 19 heifers were randomly placed in hutches (IH), and 13 stayed in a loose housing maternity pen (MP). At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Cows born in the summer showed lower milk yield and FCM yield. The most productive were cows born in the winter and spring (Broucek et al 2006). Nardone et al (1997) reported lower immunoglobulin content in the colostrum of primiparous cows exposed to heat stress prepartum.…”
Section: Discussionmentioning
confidence: 98%
“…Cows born in the summer showed lower milk yield and FCM yield. The most productive were cows born in the winter and spring (Broucek et al 2006). Nardone et al (1997) reported lower immunoglobulin content in the colostrum of primiparous cows exposed to heat stress prepartum.…”
Section: Discussionmentioning
confidence: 98%
“…Our results agree with other studies, which found that birth season is associated with milk yield after first calving, although the results are quite variable. In Slovakia, based on the results of 32 heifer calves it was found that calves born in summer had the lowest MY1, producing 1,243 kg less compared to cows born in winter [ 19 ]. Conversely, in Belgium, winter-born cows had significantly lower MY1 compared to cows born in any other season, based on the results of 74 Holstein animals [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that summer-calving heifers had the lowest, whereas autumn-calving heifers had the highest milk yield in first lactation. First calving in summer is usually associated with the lowest MY1 compared to other calving seasons [ 19 ], however, summer and autumn were associated with the highest MY1 under Belgian circumstances [ 25 ]. It is possible that in Hungary the heat stress could contribute to the lower MY1 in heifers that calved in summer, since heat stress heavily affects high-yielding dairy cows with intensive metabolism [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seasonality of milk yield in the current study was characteristic of most dairy enterprises. Earlier studies have shown that milk production varies according to animal age (Prichard and Marshall, 1983), breed (Marius et al, 2010), season and parity (Yang et al, 2013), health status (Katsande et al, 2013), lactation stage (Washaya et al, unpublished data), nutrition (Lanyasunya et al, 2005) and management (Broucek et al, 2006). Poor nutrition is largely blamed (Lanyasunya et al, 2005) for predisposing animals to diseases, and its effects on milk production and quality cannot be overemphasised.…”
Section: Janmentioning
confidence: 99%